Non-Native Bird Populations Respond Differently to Their Environment and Exhibit Shifts in Ecological Niche Limits Across Continents - Davis, Kristin P.; Sofaer, Helen R.; Smith, Henrik G. ; 0000-0002-2289-889X; Heldbjerg, Henning; Gamero, Anna; Auniņš, Ainārs; Brotons, Lluís; Chodkiewicz, Tomasz; Eskildsen, Daniel Palm; Fontaine, Benoît; Kålås, John Atle; Kmecl, Primož; et al. (Diversity and Distributions, 2025)
Aim: The degree to which species' niches remain stable over space and time–the niche conservatism hypothesis–is critical for predicting species' responses to environmental change. Tests of this hypothesis typically focus on changes in niche centroids and boundaries. An outstanding question is whether species' environmental associations differ within the interior of their niche space–that is, across the full range of occupied conditions–in original versus novel geographic space. Location: Europe and North America. Time Period: 1997–2018. Major Taxa Studied: Birds. Methods: We used over 400,000 observations collected over 22 years and across 28 countries to explore whether two common songbird species—European starling (Sturnus vulgaris) and house sparrow (Passer domesticus) – exhibit niche conservatism between their native European and non-native North American ranges. We tested for niche conservatism via (1) an ordination approach that quantified change in niche shape and boundaries, and (2) generalised linear mixed effects models to quantify how abundance varied with the interaction between continent and climate or land cover variables. Results: The ordination analysis indicated that both European starling and house sparrow exhibited niche conservatism between Europe and North America. However, abundance models revealed continental differences in how the species responded to temperature and land cover. The abundance models also revealed that areas with wetter conditions that were occupied by both species in their native European ranges were available but unoccupied in their non-native North American ranges (i.e., niche unfilling). Main Conclusions: Our work demonstrates that species can exhibit apparent consistency in niche boundaries but varied abundance responses to the environment within niche boundaries. Expanding the study of niche conservatism to explore changes both at the edge of and within niche boundaries would improve the ability to assess and predict species' invasion risk or sensitivity to ongoing global change.
Keywords: biological invasions; ecological niche; niche conservatism; Passer domesticus; range limits; Sturnus vulgaris